보건전문 대학생의 전공분야에 대한 만족도와 성격특성에 관한 연구 : 의무행정과 학생을 중심으로 - 신수옥 (연세대학교 보건대학원, 1988)
[한글] 이 연구는 보건전문대학 의무행정과 학생의 전공분야에 대한 만족도와 성격특성에 관한 연구로서 보건전문대학의 전체 7개 의무행정과 학생 450명을 대상으로 설문조사와 성격진단 검사를 자료수집 분석한 그 결과는 다음과 같다. 1. 성별에 따른 전공분야에 대한 만족도에서 여학생이 남학생에 비하여 졸업후 전공분야로 진출하기를 원하는 학생 이 더 많았고, 교내에서 이성간의 어려운 문제는 더 적었으며, 병원 현장실습에 대하여 만족하고 있는 학생은 더 많았다. 또한 여학생이 남학생에 비하여 전공학과의 변경을 더 많이 원하고 있으며, 전공과목의 강의내용, 교수의 학생지도, 전공에 대한 교수와의 상의, 교수의 인격적인 소양, 강의시설에 해하여 불만족하는 학생이 더 많았다. 2. 학년간의 전공분야에 대한 만족도에서 1학년이 2학년에 비하여 전공과목의 성적평가에 대하여 만족하는 학생이 더 많고, 강의내용에 대하여는 이해도가 낮은 학생이 더 많았다. 또한 2학년이 1학년에 비하여 교내에서 이성간의 어려운 문제가 더 적었으며 타인에게 의무행정과 입학 추천을 하기 싫어하고 전공학과의 변경을 더 많이 원하며 전공 실습과 병원 헌장실습에 대하여 불만족하고 있었다. 3. 전공분야에 대한 만족도에 영향을 미치는 요인분석에서 전공학과에 대한 만족도를 가장 유의하게 설명할 수 있는 성격특성의 변수는 적응성이었으며, 교수진에 대한 만족도에서도 적응성이었다. 또한 학교생활에 대한 만족도를 유의하게 설명할 수 있는 성격특성 의 변수들은 대응성과 사회성1 (가족관계)이었고, 전공실습에 대한 만족도를 가장 유의하게 설명할 수 있는 성격특성의 변수는 대응성 이었다. 그러나 이 연구의 제한점으로는 표본대상이 의부행정과 학생일부에 국한된 것이므로 일반화 할 수 없고, 설문지 조사방법만으로 행하여졌기 때문에 개인차가 고려되지 않았으며, 일정시점의 단면적 연구에만 의존하였다는 것이다. 앞으로 향후 연구는 훌륭한 의무기 록사 배출을 위하여 학생들의 전공분야에 대한 만족도를 충족시키는 교육과정의 연구와 학생들의 능력에 맞는 교육과정에 대한 과학적이고 구체적인 연구가 진행되어야 할것이다. [영문] The purpose of this study is to identify and analyze the level of satisfaction with major field and personality trait for the students who major medical care administration in a health junior college. The data were collected based on questionnaire survey and diagnostic examination for personality from 450 students. The results were as follows: 1. Satisfaction with the major field by sex: Comparing with male students, the more female students wanted to work in their major field after the graduation from the college. Female students had less problems with intersexual relation than male students and were more satisfied with the field practice at the hospital than sale students. However, female students wanted to change their major more so than male students and they dissatisfied more than male for the lecture contents of their fields, study guidance by professors, personal character with their professors, and learning facility such as classroom. 2. Satisfaction with the major fields by grades: Comparing with the second year students, the first year students showed more satisfaction about grading for their studies and had more difficulties with lecture contents. Also comparing with first year students, the second year students had lese problems with intersexual relation in the school, and were less likely to recommend other people to enroll to their department. Furthermore, they were more likely to change their major, and they were more dissatified with practice session both in school and hospital. 3. Analysis of factors influencing satisfaction with the field: The most significant varible on personality trait for satisfaction with the major was adaptability. The adaptability was also significant to satisfaction with teaching staffs. However, conformity and sociality Ⅰ (family relations) were significant factors influencing tole satisfaction with school life, whereas conformity was the most influencing factor for the satisfaction with the major field. This study had some limitation such as problem of generalizing the result because this study included only limited students in medical care administration. Futhermore, since this study was conducted with questionnaire survey only within certain limited timed individual differences In personal characteristics were not considered. However, this study will help improve teaching and guiding students if the further study is conducted on curriculum revision, student's adaptability, confirmity and sociality.
보건학과/석사